Analysis of graphic codes for colour representation: ColorADD and Feelipa Color Code in Portuguese companies - Iamaguti, Mariana [UNESP]; Gadotti, Marcella; Henriques, Fernanda [UNESP]; Trigueiros, Paula (John Benjamins Publishing Company, 2018)
This article is the result of initial tests and studies about two systems for chromatic representation. It introduces and discusses the use and importance of two graphic codes created in Portugal as well as their graphic application on information and communication systems in an inclusive manner for individuals with different chromatic perceptions and needs. Designed mainly for people with colour blindness and visual impairment, ColorADD and Feelipa Color Code are alternatives for colour representation via graphic and tactile mediums. From pilot tests, the application, usage and impact of these systems on society and education have been investigated via field research and interviews with their creators, developers and users.
Keywords: case study; colour; information design; social design; user centered design